Effect of Morphology and Crystal Structure on the Thermal Conductivity of Titania Nanotubes - Saima Ali (Nanoscale Research Letters, 2018)
Abstract Titania nanotubes (TNTs) with different morphology and crystal structure are prepared by chemical processing and rapid breakdown anodization (RBA) methods. The nanotubes are studied in terms of thermal conductivity. The TNTs with variable wall thickness below 30 nm have significantly reduced thermal conductivity than bulk titania, due to the phonon confinement, smaller phonon mean free path, and enhanced phonon boundary scattering. The amorphous nanotubes (TNTAmor) have comparatively thicker walls than both crystalline nanotubes. The TNTAmor has a thermal conductivity of 0.98 W m−1 K−1, which is slightly less than the thermal conductivity of crystalline anatase nanotubes (TNTA; 1.07 W m−1 K−1). However, the titania nanotubes with mixed structure (TNTA,T) and the smallest dimensions have the lowest thermal conductivity of 0.75 W m−1 K−1, probably due to the phonon confinement. The experimental results are compared with the theoretical study considering the size confinement effect with different wall dimensions of TNTs and surface scattering. The results agree well with the surface roughness factor (p) of 0.26 for TNTA,T, 0.18 for TNTA, and 0.65 for TNTAmor, indicating diffusive phonon scattering and rougher surfaces for TNTA. Interestingly, the present results together with those presented in literature suggest that thermal conductivity reduction with respect to the wall thickness occurs also for the amorphous nanotubes. This is ascribed to the role of propagons in the thermal transport of disordered structures.